pH-responsive hybrid nanoparticle with enhanced dissociation characteristic for siRNA delivery - Shi M (Dove Medical Press, 2018)
Menghao Shi,1 Xiufeng Zhao,2 Jiulong Zhang,1 Shuang Pan,1 Chunrong Yang,3 Ying Wei,1 Haiyang Hu,1 Mingxi Qiao,1 Dawei Chen,1 Xiuli Zhao1 1Department of pharmaceutics, School of Pharmacy, Shenyang Pharmaceutical University, Shenyang 110016, PR China; 2Oncology Department, Affiliated Hongqi Hospital of Mudanjiang Medical College, Mudanjiang 157000, PR China; 3Department of pharmaceutics, School of Pharmacy, Jiamusi University, Jiamusi, Heilongjiang 154007, PR China Introduction: Specific polo-like kinase (PLK1) silencing with small interface RNA (siRNA) may be an effective approach for PLK1-overexpressed lung cancer. However, low siRNA concentration into cytoplasm of tumor tissue severely limits its application.Materials and methods: In this study, a novel triblock copolymer methoxy poly(ethylene glycol)-poly(histidine)-poly(sulfadimethoxine) (mPEG-PHis-PSD, shorten as PHD) was synthesized and used to construct novel nonviral gene vector with cationic liposomes.Results: The resulting hybrid nanoparticles (PHD/LR) loaded with siPLK1 possessed excellent physiochemical properties. In vitro study indicated that PHD/LR could be efficiently internalized into human lung adenocarcinoma A549 cells and downregulated PLK1 protein expression to induce cell apoptosis, which was attributed to pH-induced instantaneous dissociation, efficient endo/lysosomal escape arose from PHD copolymer. Furthermore, in vivo antitumor activity demonstrated that PHD/LR could efficiently accumulated into tumor tissue and silenced PLK1 expression to possess antitumor activity.Conclusion: Taken all these together, PHD/LR was expected to be a suitable carrier for specific delivering siRNA for lung cancer therapy. Keywords: pH-responsive, siRNA delivery, hybrid nanoparticles, systematic evaluation